An Analysis on Evolving Legal Framework on Transgender’s Rights in Pakistan: Its Progress & Pitfalls - Wajahat, Johar; Shah, Huzaima; Gul, Seema (The Lighthouse Journal of Social Sciences, 2024)
The research paper probe in to the legal status, rights, and societal challenges faced by the transgender community in Pakistan. Despite being an integral part of society, transgender individuals continue to experience systemic discrimination, exclusion, and stigmatization, particularly in education, employment and healthcare. The research aims to explore the legal status and rights of transgender individuals in Pakistan, identify the major social, legal, and cultural issues they face and suggest effective strategies for bridging the gap between legal provisions and practical enforcement. Using a descriptive research methodology, this study relies on secondary data gathered from legal texts, academic journals, court decisions, and relevant articles to analyze the transgender community’s current condition in light of national laws and Islamic interpretations. The results highlight that although Pakistan enacted the Transgender Persons (Protection of Rights) Act in 2018, its implementation remains weak. Discriminatory practices continue due to social taboos, poor awareness, outdated policies, and a lack of political will. Key areas such as CNIC (Computerized National Identity Card) registration, workplace harassment protection, educational quotas, and media representation remain unheeded. In conclusion, while some legal reforms exist on paper, Pakistan has a long way to go in translating legislation into action. Recommendations include reviewing existing laws, ensuring provincial implementation, creating representation quotas, recognizing international conventions, and involving media in reshaping public perception. This research underscores the need for comprehensive legal, social, and institutional reforms to secure equality, dignity, and justice for transgender people in Pakistan.